Golden potato cyst nematode and controls it's size - Babich, A.; Babich, A.; Statkevich, A.; Bondar, V. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2018)
Reliable protection against the Golden potato cyst nematode is one of the reserves for increasing potato yield in Ukraine. Compliance with the main provisions of the improved monitoring ensures timely detection of globoderosis foci, and the introduction of a set of protective measures in farms prevents further resettlement of the quarantine organism and significant crop losses.